Health Burden and Socioeconomic Disparities From Hearing Loss: A Global Perspective. Issue 1 (January 2018) - Ramsey, Tam; Svider, Peter F.; Folbe, Adam J.
Abstract : Objectives/Hypothesis: To characterize the disability-related health burden of hearing loss (HL) at a global level, with a focus on socioeconomic health disparities. Methods: The global burden of HL, as calculated by disability-adjusted life years (DALYs) per 100, 000 individuals, was evaluated for 184 countries. Data from 5-year intervals encompassing 1990 to 2015 were organized by human development index (HDI) categorizations as specified by the U.N. Development Program (UNDP). Gini coefficients and concentration indices were used to evaluate global inequality in HL burden over this time period. Results: There was a global lack of improvement in hearing loss burden over 25 years. National HL burden, as measured by age-standardized DALYs, had an inverse relationship with successive level of development ( p  < 0.0001). Global inequalities in HL burden as measured by the concentration index decreased from 1990 to 2005, remained stable between 2005 and 2010, and slightly increased from 2010 to 2015. Central Sub-Saharan Africa, followed by Eastern Sub-Saharan Africa and South Asia, had the greatest rates of disease burden in 2015. Conclusions: To our knowledge, this analysis is the first to investigate socioeconomic-related inequalities in hearing loss burden using statistical tools such as the Gini coefficient and concentration index. Although inequalities have largely decreased in recent decades, the global burden of hearing loss remains high and there are recent signs of increased inequality. These data suggest that a greater distribution of hearing care resources may need to be directed towards developing countries to combat global hearing loss burden. Level of Evidence: III